The effect of non‐contact electro capacitive cancer therapy on DMBA‐induced rat breast tumor angiogenesis - Endah Sri Palupi; Bambang Retnoaji; Pudji Astuti; Firman Alamsyah; Warsito Purwo Taruno; Rarastoeti Pratiwi (Universitas Gadjah Mada, 2024)
Alternating Current‐Electric Field (AC‐EF) generated by non‐contact Electro Capacitive Cancer Therapy (ECCT) can inhibit breast tumor growth. However, its effect on breast tumor angiogenesis remains unclear. Since angiogenesis is involved in normal physiology and tumors, it is crucial to investigate the effect of ECCT on normal and breast tumor angiogenesis. Samples consisting of rat breast normal tissue and breast tumors were obtained from the biobank, with tumors induced by 7,12‐dimethylbenz (α) anthracene (DMBA) at 20 mg/kg BW 10 times over five weeks. Meanwhile, ECCT exposure of 150 kHz and 18 Vpp was conducted for 21 days at 10 hours/day. The qPCR method was used for gene expression analysis, while immunohistochemistry used antibody anti‐Vegfr2 that was used to detect Vegfr2 protein expression. Data were analyzed using one‐way ANOVA and t‐tests performed with GraphPad Prism ver.9.5.1 software. The results revealed no impact of ECCT exposure on normal breast tissue angiogenesis. Interestingly, there was a significant increase in the number of blood vessels following the upregulation of Vascular Endothelial Growth Factor Receptor‐2 (Vegfr2) as opposed to its primary signal, Vascular Endothelial Growth Factor‐A (Vegfa). Furthermore, gene expression of Hypoxia Inducible Factor‐1α (Hif1α) and Specificity Protein‐1 (Sp1) was similar to that of the control group, suggesting that Vegfr2‐dependent angiogenesis regulates ECCT‐treated breast tumor angiogenesis.